Pembatasan Sosial Berskala Besar dan Pemulihan Ekonomi Nasional di Masa Pandemi Covid-19: Strategi Implementasi Peraturan Perundang-Undangan - Asmah Asmah; Dian Eka Kusuma Wardani; Raodiah Raodiah (CV. Social Politic Genius (SIGn), 2021)
This study aims to determine the Government’s strategy in making regulations related to health problems and economic problems for the community. In addition, this study also wants to know the impact of Makassar Municipality’s strategy in implementing regulations to increase the productivity and competitiveness of the community and business actors during the Covid-19 pandemic. This study uses two types of research: normative research and empirical research. In-depth interviews, literature review, and documentation are data collection techniques used in this research. The data that has been collected is then processed and analyzed using qualitative descriptive analysis techniques. The results show that the Government’s priority in dealing with the Covid-19 problem is establishing Government Regulation No. 21 of 2020 to address national health issues. Meanwhile, the Government’s priority in dealing with community economic problems is establishing Law No. 7 of 2021. In this case, the Government relaxes VAT payments and SPT reporting to individuals and business actors. Furthermore, the impact of the Mayoral Regulation of Makassar Municipality No. 51 of 2020 is the decline in people’s economic income during the Covid-19 pandemic. However, with the Mayoral Regulation of Makassar Municipality No. 51 of 2020, people can still carry out economic activities by complying with health protocols. Therefore, it is recommended that the people of Makassar Municipal continue to carry out economic activities by complying with health protocols even though they are currently entering the new normal period. In addition, business actors who have received relaxation of VAT payments and SPT reporting and their businesses have reached a stable condition to fulfill their obligations again by paying taxes. Paying taxes is a form of community participation in national development.